STUDI KUALITATIF MENGENAI PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI DINI DI DUSUN PACIRAN, DESA PACIRAN, KABUPATEN LAMONGAN - Wahdah, Lady Nubailah; Ruhana, Amalia (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
Complementary feeding (CF), or complementary food, refers to the food or beverages given to infants or children aged 6-24 months to meet their nutritional needs alongside breast milk. It is introduced at around six months of age to provide additional energy and other dietary requirements. However, incorrect practices in introducing CF, such as early introduction, are still prevalent. This research explores factors that influence the early introduction of CF in Paciran Hamlet, Paciran Village, Lamongan Regency. This study employs a qualitative descriptive research design, utilizing in-depth interviews for data collection. The research was conducted in Paciran Hamlet in August 2022, involving 3 main informants selected through purposive sampling and two supporting informants selected through snowball sampling. Data analysis was performed using the content analysis method, and the findings were presented as descriptive narratives. The results of this study revealed that factors that can strengthen mothers in providing CF on time in Paciran Hamlet are the knowledge of mothers and their families regarding CF. On the other hand, factors influencing mothers to introduce CF in Paciran Hamlet, Paciran Village, Lamongan Regency: 1) Mothers' perception that their child is sufficiently mature to consume solid food, 2) Motivation, 3) Family and environmental support, 4) Cultural factors, 5) Healthcare professionals, 6) Compliance with Posyandu, 7) Individuals involved in childcare, 8) Mothers' job. It is crucial to provide education and raise awareness regarding CF, establish monitoring and evaluation processes related to the early introduction of CF practices, and conduct further research in this area.